2018
DOI: 10.1007/s40094-018-0299-7
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz optical bistability of graphene-coated cylindrical core–shell nanoparticles

Abstract: In this study, we investigate the optical bistability of graphene-coated nanoparticles with cylindrical core-shell structure at terahertz frequency, because graphene displays optical bistability and multistability in a broad range of incident optical intensity. The choice of core-shell system is due to its larger local electric field enhancement, where this characteristic is important for the optical bistable systems. This optical bistability strongly depends on the geometry of the nanoparticle, the fractional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This is yet another critical outcome of our investigation. These kinds of ramp like bistable states are already observed in plasmon resonance structures [53,54], graphene based structures [55,56], silicon waveguide resonators [57] and plexcitonic systems [58]. But this is the very first time such a OB/OM is observed in a PT -symmetric FBG device, thanks to the judicious balance between the gain and loss.…”
Section: Broken Pt -Symmetric Regime a Influence Of Gain/loss Parametermentioning
confidence: 78%
“…This is yet another critical outcome of our investigation. These kinds of ramp like bistable states are already observed in plasmon resonance structures [53,54], graphene based structures [55,56], silicon waveguide resonators [57] and plexcitonic systems [58]. But this is the very first time such a OB/OM is observed in a PT -symmetric FBG device, thanks to the judicious balance between the gain and loss.…”
Section: Broken Pt -Symmetric Regime a Influence Of Gain/loss Parametermentioning
confidence: 78%
“…To conclude, compared to the relevant studies of the optical bistability behavior in the THz for simpler systems such as graphene-coated cylindrical core-shell nanoparticles [24], graphene in thin layers of dielectrics [25] and graphene sheets [26], our proposed plasmonics system shows ultralow thresholds of the controllable optical bistability even though we have used small Fermi energy compared to those used in the indicated studies. Interestingly, it is expected that increasing the Fermi energy will enhance the nonlinearity of the system due to the large plasma frequency of graphene in such cases.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been shown that the linear dispersion properties of graphene should result in strong nonlinear optical behavior at the microwave and THz frequencies [20,21]. Consequently, nonlinear phenomena such as optical bistability have recently been studied for several graphene-based materials in order to achieve low thresholds and efficient optical control at the THz frequencies [22][23][24][25][26]. Specifically, the optical bistability has theoretically been investigated for graphene-wrapped dielectric composite at THz frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…2(a) with the main difference that the slope of the OB curves is now almost unity and thus we obtain ramp-like stable states in the broken PT -symmetric regime. Previously, it was reported that physical systems involving plexcitons [54], graphene [55,56], and plasmons [57,58] are the only known structures whose input-output characteristics show ramp like stable states. Recently, we have demonstrated that a broken PT -symmetric uniform FBG can exhibit such unique stable states as a result of delicate balance between the gain and loss [49,59].…”
Section: B Left Incidence: Broken Pt -Symmetric Regimementioning
confidence: 99%